INNOVATING URBAN ENVIRONMENTAL CONSERVATION THROUGH COMMUNITY-BASED MURAL INITIATIVES IN PERENG, CENTRAL JAVA - Desy Nurcahyanti; Deny Tri Ardianto; Mohd Asyiek Mat Desa; Khwanrat Chinda (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Aim: This study aims to find out how the Pereng community receives education about environmental conservation and cultural creativity through murals, which villagers are familiar with, to ease the burden in terms of cleanliness, for example, dry leaves that fall to the ground because they will rot into compost by natural processes. Methodology and results: The quality of water and soil around Pereng is decreasing based on research results from a team from the Faculty of Agriculture, Universitas Sebelas Maret. Somebody took a series of approaches, including outreach from the Department of Regency Health. The Pereng people have the character of being able to easily receive information through an arts and cultural approach that is close to their lives. Direct socialization methods tend to be unacceptable because they are judgmental. Conclusion, significance, and impact study: This study show that sensitive people prefer mural images as a means of education compared to direct socialization, which takes up their activity time, are easier to interpret, and are non-judgmental. The Pereng people's busy lives as farmers and traders have been entertained by rich, colorful, and shape murals. The Pereng Creative Village pilot requires strengthening so that somebody can quickly understand the dynamic character of the Pereng community. Murals are an attractive visual medium to explain calls for environmental awareness through two-dimensional images. Murals scattered at several points in Pereng Village represent the village's nature, agricultural products, arts and culture, and productive activities of the community, such as planting rice.